1999
DOI: 10.1063/1.479300
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-laser induced desorption of NO from the Cr2O3(0001) surface: Involvement of a precursor state?

Abstract: A joint theoretical-experimental investigation of the lower bound states of the NO (X 2 Π)-Ar complex NO molecules interact with the Cr 2 O 3 (0001) surface to form a chemisorption bond of 1.0 eV. At higher coverages an additional more weakly bound species appears in thermal desorption spectra with a binding energy of 0.35 eV. By infrared spectroscopy the weakly adsorbed species is identified to be an unusually strong bound NO-dimer exhibiting a weak feature at 1857 cm Ϫ1 beside the chemisorbate absorption ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…The observations described above can be interpreted on the basis of previous work on NO adsorption on different oxide [41][42][43] and metal surfaces (see refs. 43-51 and references therein).…”
Section: No Interaction With the Pristine Al 2 O 3 Model Supportmentioning
confidence: 77%
“…The observations described above can be interpreted on the basis of previous work on NO adsorption on different oxide [41][42][43] and metal surfaces (see refs. 43-51 and references therein).…”
Section: No Interaction With the Pristine Al 2 O 3 Model Supportmentioning
confidence: 77%
“…Lastly, the appearance of the peak at 1885 cm −1 occurs at coverages at which the NO TPD spectra begin to exhibit peaks below about 170 K. Wilde et al have reported analogous behavior in the adsorption of NO on a Cr 2 O 3 (0001) surface and show that NO dimers are responsible for the weak RAIRS peak near 1885 cm −1 . 40 To further investigate the N−O stretch bands that arise from the different NO binding states on Fe 3 O 4 (111), we collected RAIR spectra after heating an NO layer to different temperatures. Figure 4b shows RAIR spectra obtained after preparing a saturated NO layer at 87 K and heating the surface to temperatures of 170 and 315 K, where these temperatures are selected to desorb NO from the predominant states revealed by TPD (Figure 3).…”
Section: ■ Resultsmentioning
confidence: 99%
“…The photodesorption of NO has also been studied [279]. The photodesorption of NO has also been studied [279].…”
Section: Mo Momentioning
confidence: 99%